2006
DOI: 10.1159/000096413
|View full text |Cite
|
Sign up to set email alerts
|

Chronic (–)-Deprenyl Administration Attenuates Dendritic Developmental Impairment Induced by Early Social Isolation in the Rat

Abstract: It has been demonstrated that postweaning social isolation alters dendritic development in the medial prefrontal cortex (mPFC) of the rat. In addition, (–)-deprenyl, a monoamine oxidase B (MAO-B) inhibitor, promotes dendritic growth in prefrontocortical pyramidal cells. This study examined whether prefrontocortical dendritic developmental impairment induced by postweaning social isolation is attenuated by chronic (–)-deprenyl administration. Weanling Sprague-Dawley male rats were randomly reared in social and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…In addition, it has been shown that SEL promotes dendritic outgrowth in frontal, hippocampal, mesencephalic and spinal neurons (Iwasaki et al, 1994;Kontkanen and Castrén, 1999;Lakshmana et al, 1998;Shankaranarayana-Rao et al, 1999), suggesting trophic-like actions. Likewise, in a previous study we were able to demonstrate that SEL can partially recover cortical dendritic outgrowth impairments induced by post-weaning isolation stress (Pascual and Zamora-León, 2007).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, it has been shown that SEL promotes dendritic outgrowth in frontal, hippocampal, mesencephalic and spinal neurons (Iwasaki et al, 1994;Kontkanen and Castrén, 1999;Lakshmana et al, 1998;Shankaranarayana-Rao et al, 1999), suggesting trophic-like actions. Likewise, in a previous study we were able to demonstrate that SEL can partially recover cortical dendritic outgrowth impairments induced by post-weaning isolation stress (Pascual and Zamora-León, 2007).…”
Section: Introductionsupporting
confidence: 65%
“…On the other hand, lower expression of CB in the cerebral cortices of animals treated with SEL suggest that at least one of the neuroprotective effects of selegiline occurs through the increased efficiency of target neurons in buffering Ca 2+ overload, as indirectly evidenced by CB down‐regulation. In the current study, we used a dose of SEL (0.2 mg kg −1 ) that, as shown in previous works, produced neurotrophic and neuroprotective effects (Kontkanen and Castrén, 1999; Lakshmana et al, 1998; Shankaranarayana‐Rao et al, 1999; Pascual and Zamora‐León, 2007). Considering the neuroprotective and neurotrophic effects of SEL described in previous studies, we believe that SEL should not be dismissed as a potent neuroprotective drug without an exhaustive assessment of its dose‐related effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the neurobiological changes in the brain of isolation‐reared rats resemble those seen in the schizophrenic patient, hence the model has good construct validity. For example, as in schizophrenic patients (Hirayasu et al ., 2001; Harrison, 2004), a selective reduction in PFc volume occurs in isolation‐reared rats (Day‐Wilson et al ., 2006; Schubert et al ., 2009) accompanied by decreased dendritic spine density and morphology (Silva‐Gomez et al ., 2003; Pascual and Zamora‐Leon, 2007), cytoskeletal alterations (Bianchi et al ., 2006) and reduced parvalbumin and calbindin‐containing GABAergic chandelier cartridges (Harte et al ., 2007; Bloomfield et al ., 2008) of hippocampal and PFc interneurones. The age of commencing isolation rearing and gender both interact to affect the extent of change in dendritic spine morphology and complexity that develops in PFc, anterior cingulate and orbitofrontal cortices (Ferdman et al ., 2007).…”
Section: Neurodevelopmental Modelsmentioning
confidence: 99%
“…Chronic administration of another MAOI (−)-deprenyl prevents the dendritic impairments of rat PFC pyramidal neurons caused by social isolation stress (Pascual and Zamora-Leon, 2007). In a very recent study rats treated for 10 days with 9-Methyl- β -carboline, which inhibits MAO-A but also has other effects on monoamine transmission, improved spatial learning in the radial maze and increased dendrite complexity and spine number on dentate gyrus granule cells (Gruss et al, 2012).…”
Section: Remodeling Of Spine and Dendrite Architecture By Antideprmentioning
confidence: 99%